2023
DOI: 10.3389/fbioe.2023.1189010
|View full text |Cite
|
Sign up to set email alerts
|

In situ gelling hydrogel loaded with berberine liposome for the treatment of biofilm-infected wounds

Abstract: Background: In recent years, the impact of bacterial biofilms on traumatic wounds and the means to combat them have become a major research topic in the field of medicine. The eradication of biofilms formed by bacterial infections in wounds has always been a huge challenge. Herein, we developed a hydrogel with the active ingredient berberine hydrochloride liposomes to disrupt the biofilm and thereby accelerate the healing of infected wounds in mice.Methods: We determined the ability of berberine hydrochloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Berberine is an isoquinoline derivative with anti-inflammatory and antimicrobial properties, which has been used for treating wound healing when embedded in vesicle carriers, gel delivery systems, and cream formulations [ 122 , 123 , 124 ]. This method of encapsulating drugs into vesicles and encapsulating vesicles into semi-solid formulations (hydrogels) has been confirmed to be an important strategy to circumvent the drawbacks of nanovesicles, and the sequestration of such systems in polymer matrices provides a means of further controlling the spatial and temporal release of drugs [ 125 , 126 ].…”
Section: Preparation and Antimicrobial Properties Of Ss Antimicrobial...mentioning
confidence: 99%
“…Berberine is an isoquinoline derivative with anti-inflammatory and antimicrobial properties, which has been used for treating wound healing when embedded in vesicle carriers, gel delivery systems, and cream formulations [ 122 , 123 , 124 ]. This method of encapsulating drugs into vesicles and encapsulating vesicles into semi-solid formulations (hydrogels) has been confirmed to be an important strategy to circumvent the drawbacks of nanovesicles, and the sequestration of such systems in polymer matrices provides a means of further controlling the spatial and temporal release of drugs [ 125 , 126 ].…”
Section: Preparation and Antimicrobial Properties Of Ss Antimicrobial...mentioning
confidence: 99%
“…[19] This necessitates the development of novel drug delivery materials to optimize drug efficacy and mitigate antimicrobial resistance. [20] Berberine hydrochloride (BBH) is an isoquinoline alkaloid with diverse biological activities, including antibacterial, anticancer, anti-inflammatory, and antioxidant effects. [21] BBH exhibits broad-spectrum antibacterial activity against various Gram-negative and Gram-positive bacteria, [22] particularly demonstrating pronounced inhibitory effects on Staphylococcus aureus, Streptococcus hemolyticus, Vibrio cholera, Salmonella typhi and Corynebacterium diphtheriae.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that death caused by bacterial infection is the second leading cause of death in the world, and the emergence of antimicrobial resistance (AMR) poses a growing global crisis due to increasing bacterial resistance to existing drugs [19] . This necessitates the development of novel drug delivery materials to optimize drug efficacy and mitigate antimicrobial resistance [20] . Berberine hydrochloride (BBH) is an isoquinoline alkaloid with diverse biological activities, including antibacterial, anticancer, anti‐inflammatory, and antioxidant effects [21] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations